Increased binding of peripheral benzodiazepine receptor in mild cognitive impairment–dementia converters measured by positron emission tomography with [11C]DAA1106 - Yasuno, Fumihiko; Kosaka, Jun; Ota, Miho; Higuchi, Makoto; Ito, Hiroshi; Fujimura, Yota; Nozaki, Shoko; Takahashi, Sho; Mizukami, Katsuyoshi; Asada, Takashi; Suhara, Tetsuya (Psychiatry research. Neuroimaging, 2012)
Subjects with mild cognitive impairment (MCI) have “prodromal or incipient” dementia with neuropathological changes. Peripheral benzodiazepine receptor (PBR) binding was shown to reflect activated microglia, one of the predictive biomarkers of conversion to dementia. We sought to evaluate PBR binding in MCI subjects using positron emission tomography (PET). PET scans with [11C]DAA1106, a potent and selective ligand for PBR, were performed on seven MCI subjects, 10 patients with Alzheimer's disease (AD) and 10 age-matched control subjects. PBR binding in the regions of interest was quantified by binding potential (BP). Five MCI subjects were clinically followed for 5years after their initial PET scans. [11C]DAA1106 binding to PBR was significantly increased in widespread areas in MCI subjects when compared to healthy controls. We found no significant difference in BP between MCI and AD patients. MCI subjects with [11C]DAA1106 binding values higher than the control mean +0.5 standard deviation (S.D.) developed dementia within 5years. Our finding of higher DAA binding in MCI subjects indicated that microglial activation may occur before the onset of dementia. In vivo detection of microglial activation may provide useful prognostic information with respect to stratifying MCI subjects at increased risk of dementia.